Structure of zebrafish IRBP reveals fatty acid binding. (November 2015) - Ghosh, Debashis; Haswell, Karen M.; Sprada, Molly; Gonzalez-Fernandez, Federico
Abstract: Interphotoreceptor retinoid-binding protein (IRBP) has a remarkable role in targeting and protecting all- trans and 11- cis retinol, and 11- cis retinal during the rod and cone visual cycles. Little is known about how the correct retinoid is efficiently delivered and removed from the correct cell at the required time. It has been proposed that different fatty composition at that the outer-segments and retinal-pigmented epithelium have an important role is regulating the delivery and uptake of the visual cycle retinoids at the cell-interphotoreceptor-matrix interface. Although this suggests intriguing mechanisms for the role of local fatty acids in visual-cycle retinoid trafficking, nothing is known about the structural basis of IRBP-fatty acid interactions. Such regulation may be mediated through IRBP's unusual repeating homologous modules, each containing about 300 amino acids. We have been investigating structure-function relationships of Zebrafish IRBP (zIRBP), which has only two tandem modules (z1 and z2), as a model for the more complex four-module mammalian IRBP's. Here we report the first X-ray crystal structure of a teleost IRBP, and the only structure with a bound ligand. The X-ray structure of z1, determined at 1.90 Å resolution, reveals a two-domain organization of the module (domains A and B). A deep hydrophobic pocket with a single bound molecule of oleic acid was identified within the N-terminal domain A. In fluorescence titrations assays, oleic acid displaced all- trans retinol from zIRBP. Our study, which provides the first structure of an IRBP with bound ligand, supports a potential role for fatty acids in regulating retinoid binding. Highlights: Fatty acids have been proposed to regulate retinoid trafficking by IRBP. However, nothing is known about the structure of IRBP-fatty acid interactions. We determined the X-ray crystal structure of the zebrafish IRBP module one (z1). Z1 consists of domains A & B with a novel oleic acid binding pocket in domain A. The holoIRBP structure is consistent with fatty acids regulating retinoid trafficking.